43. PATIENT’S QUALITY OF LIFE HAVING ALMOST TOTAL STOMACH SURGERY FOR CANCER AT TAN TRIEU DEPARTMENT OF EXAMINATION, K HOSPITAL 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: The study aimed to examine the quality of life and some factors affecting patients' quality of life after near-total gastric surgery for cancer at Tan Trieu Department of Examination, K Hospital.Materials and methods: A cross-sectional descriptive analysis of 220 patients who had near-total-thickness surgery at Tan Trieu Department of Examination, utilizing the EORTC QLQ-C30 and QLQ-STO22 instruments.Results: The overall quality of life index is 62.5 points. Quality of life ratings in symptom areas are 27.78 points for exhaustion, 33.33 for sleeplessness, and 16.67 for pain. The financial difficulty score is 66.67 points. Age group, gender, location of residence, occupation, economic burden, and the patient's symptoms all influence the patient’s quality of life.Conclusion: Patients who have near-total gastric surgery have a somewhat low overall quality of life are 6.25 pionts. It is vital to pay attention, closely monitor and treat the patient's symptoms, impart health education, and advise on suitable nutrition and exercise, all of which contribute to the patient's overall quality of life
Keywords: Stomach cancer; quality of life; near-total gastric surgery